Piękno świata stworzonego według św. Augustyna - Jaśkiewicz, Sylwester (Vox Patrum, 2024)
The beauty of the world created, by Saint Augustine has been significantly enhanced, especially through inspiration coming from philosophy and biblical exegesis. The Bishop of Hippo was deeply convinced of the beauty (pulchritudo, pulchrum, species) of the visible world. The basic elements of the structure of every being, and therefore also of its beauty, include: number (numerus), measure (mensura), weight (pondus) and order (ordo). The beauty of the created world is the beauty that includes the visible world, man and angels. Both all creatures and each of them individually and in all their diversity are a song of praise to God the Creator, the Supreme Good and Beauty, who is a great Artist (artifex magnus).